2020
DOI: 10.1016/j.ebiom.2020.102834
|View full text |Cite
|
Sign up to set email alerts
|

Decreased salivary lactoferrin levels are specific to Alzheimer's disease

Abstract: Background Evidences of infectious pathogens in Alzheimer's disease (AD) brains may suggest a deteriorated innate immune system in AD pathophysiology. We previously demonstrated reduced salivary lactoferrin (Lf) levels, one of the major antimicrobial proteins, in AD patients. Methods To assess the clinical utility of salivary Lf for AD diagnosis, we examine the relationship between salivary Lf and cerebral amyloid-β (Aβ) load using amyloid-Positron-Emission Tomography (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 73 publications
6
49
1
Order By: Relevance
“…Technology is now available to extract neuronal exosomes within blood 143 , making them an important prospect for future studies. Lastly, other body fluids poorly studied as potential sources of biomarkers in FTD are urine 144 or saliva 145 , and future studies would benefit from investigating these further.…”
Section: Resultsmentioning
confidence: 99%
“…Technology is now available to extract neuronal exosomes within blood 143 , making them an important prospect for future studies. Lastly, other body fluids poorly studied as potential sources of biomarkers in FTD are urine 144 or saliva 145 , and future studies would benefit from investigating these further.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, brain shows the presence of lactoferrin which substantially increases in AD patients. It is also correlated with the AD pathogenesis because of the direct relation with microgila of brain, amyloid beta plaques, and NFT of patients [91,92]. Although, there are [19], and b Multiplex detection of Aβ42 peptide and t-Tau protein using graphene-based field effect transistor (gFET) biosensor.…”
Section: Detection Of Ad Biomarkers In Biosamplesmentioning
confidence: 99%
“…Additionally, brain shows the presence of lactoferrin which substantially increases in AD patients. It is also correlated with the AD pathogenesis because of the direct relation with microgila of brain, amyloid beta plaques, and NFT of patients [ 91 , 92 ]. Although, there are various AD related biomolecules in secretions of salivary glands, the conclusiveness of the results is still limited due to the lack of proper and sufficient standardization [ 93 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences in salivary lactoferrin levels between MCI-PET positive and AD patients and between controls and MCI-PET negative groups. These results revealed that decreased salivary lactoferrin levels are AD-specific biomarkers and are helpful in differentiating and diagnosing the early clinical stages of AD, as well as in predicting the development and progression of cognitive disorders in AD [ 51 ].…”
Section: Biomarkers In the Diagnosis Of Alzheimer’s Diseasementioning
confidence: 99%